Effects of post-harvest treatments and packaging materials on physico chemical properties and shelf-life of guava (Psidium guajava) - Meena, Suman; Singh, S. P.; Garhwal, O.P.; Jangid, Tulsi Ram (Current Horticulture, 2025)
The study was undertaken to find out efficacy of different post-harvest treatments and packaging materials on improving the quality and shelf-life of guava fruits variety Allahabad Safeda at post-harvest laboratory, Department of Horticulture, SKN College of Agriculture, Jobner, during 2022-23 and 2023-24. The fruits were subject to dipping in tap water for 3 minutes, oxalic acid (OA) 10 mM 3 min., salicylic acid (SA) 2.0 mM 3min., calcium chloride at 1.5% 3min., with different packaging material, polythene bag (LDPE 25 Micron), corrugated boxes, gunny bag and untreated fruits without packing. The fruits were stored at ambient storage conditions for 12th days. Fruits were analyzed for various physico-chemical characteristics, viz., PLW, decay percentage, shelf life, TSS, acidity, ascorbic acid, reducing, non-reducing and total sugars at an interval of 0, 4, 8 and 12 days. The results revealed that perforated calcium chloride 1.5% with polythene bag was the most effective in reducing weight loss and decay as compared to other treatments. Total soluble solids, reducing sugars, total sugars and ascorbic acid content were higher in fruits stored in perforated calcium chloride with polythene bag and it was also effective in extending the shelf -life of guava fruits to 13 days. Thus, it can be concluded that perforated calcium chloride 1.5 % with polythene bag can be recommended for extending storage period of guava fruits.